The study of some issues of the application of cryptocurrency mining technology in Kazakhstan - Sabyrzhan, A.; Orynbassarova, Ye.D.; Zhakupov, A.A.; Khamitova, D.M.; Gelashvili, N.N. (BUKETOV BUSINESS REVIEW, 2024)
Object: Analyze the use of cryptocurrency mining technology in Kazakhstan and develop recommendations for improving its effective operation. Methods: We have used scientific methodological and research approaches, such as comparison, grouping, analysis, classification, statistical data, induction, deduction, economic-mathematical methods, and modeling. Findings: The study’s practical significance is that these principles and approaches can be used to form a mining farm development strategy. The proposals presented will improve the digital efficiency of the company and stabilize and improve its financial and economic situation by making appropriate management decisions. The study results make it possible to solve problems related to the ability of enterprises to provide a medium and long-term stable position in the market and flexibly adapt to the environment. Conclusions: Based on the study, the concept of “cryptocurrency”, “mining”, and “mining farm” was clarified as a particular form of a new information economy and society that combines its input stages of the technological chain or stages of its release in order to achieve significant competitive advantages compared to specialized types of digital money. The features of digital money, such as cryptocurrencies and their mining, which include various platforms, objects, and types but have common elements, technologies, development management, and risks, were identified. A methodology for analyzing the IT architecture of cryptocurrency and the volatility of the digital currency is proposed, which allows one to find out quantitative and qualitative indicators, assess the extensiveness, intensity, and efficiency of the use of cryptocurrency, and determine the reserves for its full use.